Safe Introduction of Minimally Invasive Esophagectomy at a Medium Volume Center. (June 2020) - Linder, G.; Jestin, C.; Sundbom, M.; Hedberg, J.
Background and Aims: Minimally invasive esophagectomy is a favored alternative in high-volume centers. We evaluated the introduction of, and transition to, minimally invasive esophagectomy at a medium volume tertiary referral center (10–20 esophagectomies annually) with focus on surgical results. Material and Methods: Patients who underwent minimally invasive esophagectomy or open transthoracic surgery for carcinoma of the esophagus or gastroesophageal junction (Siewert I and II) during 2007–2016 were retrospectively studied. Sorted on surgical approach, perioperative data, surgical outcomes, and postoperative complications were analyzed and multivariate regression models were used to adjust for possible confounders. Results: One hundred and sixteen patients were included, 51 minimally invasive esophagectomy (21 hybrid and 30 totally minimally invasive) and 65 open resections. The groups were well matched. However, higher body mass index, neoadjuvant chemoradiotherapy, and cervical anastomosis were more frequent in the minimally invasive esophagectomy group. Minimally invasive esophagectomy was associated with less peroperative bleeding (384 vs 607 mL, p = 0.036) and reduced length of stay (14 vs 15 days, p = 0.042). Duration of surgery, radical resection rate, and postoperative complications did not differ between groups. Lymph node yield was higher in the minimally invasive esophagectomy group, 18 (13–23) vs 12 (8–16), p < 0.001, confirmed in a multivariate regression model (adjusted odds ratio 3.15, 95% class interval 1.11–8.98, p = 0.032). Conclusion: The introduction of minimally invasive esophagectomy at a medium volume tertiary referral center resulted in superior lymph node yield, less peroperative blood loss and shorter length of stay, without compromising the rate of radical resection, or increasing the complication rate.